SUSTAINABILITY FADs MANAGEMENT ON ECONOMIC DIMENSION IN THE KEI ISLANDS SOUTHEAST MALUKU REGENCY - Benny Jeujanan; Sulaeman Martasuganda; M. Fedi A. Sondita; Roza Yusfiandayani; Daniel Monintja (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Fish aggregating devise (FAD) based fisheries have become a dominant economic support (about 90%) of the community of the Kei Islands in Southeast Maluku Regency. However, it will not last long if the fisheries is not well managed and financially balanced. This study aimed to analyze the attributes of sustainable FADs-based. fisheries and to assess the financial feasibility for an investment. The method used was the analysis of FADs investment, the consumption and income of the fishermen’s households of mini purse seine and FADs, contribution to the local revenues, and the growth of fishing supporting business. The analyses results showed that the investment for a FADs was of Rp. 13,714,000, mini purse seine of Rp. 426,875,000, handline of Rp. 71,75 million, and troll lines of Rp. 72,75 million, household consumption of Rp. 13,625,730. The income of FAD fisherman was of Rp. 164,143,125, mini purse seine fisherman of Rp. 164,143,125, and entrepreneur of Rp. 328,286,250. The index value of the sustainable FAD management was 62.17 indicating a sustainable index. Keywords: FAD (Fish aggregating device), Kei Islands, Management, Sustainability